Dampak Penggunaan Handphone terhadap Karakter Tanggung Jawab kepada Diri Sendiri Peserta Didik di SMK Negeri 1 Rao Selatan - Susanti, Esti; Rahman, Rini (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2023)
The purpose of this researc is to determine the positive and negative impacts of the use of mobile phones on the character of self-responsibility of students at SMK Negeri 1 Rao Selatan. The research method used is a qualitative method with a case study approach. Data collection methods used are observation and interview methods. The data analysis technique used is data reduction, data presentation and drawing conclusions. Based on the results of the research and discussion, it can be concluded that 1) there is a positive impact on the character of self-responsibility of students, namely a) on their bodies (cleanliness, eating and drinking, and health) b) on their minds (studying knowledge and practicing knowledge in life) c) on their souls (repent and abstain from major sins and mujahadah) 2) there is a negative impact on the character of self-responsibility of students, namely a) on their bodies (cleanliness, eating and drinking, health, and wearing syar'i clothing /covering the genitals) b) against his mind (studying knowledge) c) against his soul (repent and abstain from major sins).